Indigeneity in real time : the digital making of Oaxacalifornia - Kummels, Ingrid (New Brunswick : Rutgers University Press, 2023)
"Long before the COVID-19 crisis, Mexican Indigenous peoples were faced with organizing their lives from afar, between villages in the Oaxacan Sierra Norte and the urban districts of Los Angeles, as a result of unauthorized migration and the restrictive border between Mexico and the United States. By launching cutting-edge Internet radio stations and multimedia platforms and engaging as community influencers, Zapotec and Ayuujk peoples paved their own paths to a transnational lifeway during the Trump era. This meant adapting digital technology to their needs, setting up their own infrastructure, and designing new digital formats for re-organizing community life in all its facets-including illness, death and mourning, collective celebrations, sport tournaments, and political meetings-across vast distances. Author Ingrid Kummels shows how mediamakers and users in the Sierra Norte villages and in Los Angeles created a transborder media space and aligned time regimes. By networking from multiple places, they put into practice a communal way of life called Comunalidad and an indigenized American Dream-in real time"--
Introduction: community life and media in times of crisis -- Histories of mediatic self-determination -- Zapotec dance epistemologies online -- The fiesta cycle and transnational death on internet radio -- Ayuujk basketball tournament broadcasts: expanding transborder community interactively -- Turning fifteen transnationally: the politics of family movies and digital kinning -- Epilogue: Reloading comunalidad-Indigeneity on the ground and on the air.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed April 7, 2023).
JSTOR
Keywords: Zapotec Indians -- California -- Los Angeles -- Social conditions; Zapotec Indians -- Mexico -- Sierra Norte (Oaxaca) -- Social conditions; Mixe Indians -- California -- Los Angeles -- Social conditions; Mixe Indians -- Mexico -- Sierra Norte (Oaxaca) -- Social conditions; Internet and Indigenous peoples -- California -- Los Angeles; Internet and Indigenous peoples -- Mexico -- Sierra Norte (Oaxaca); Communication and culture -- California -- Los Angeles; Communication and culture -- Mexico -- Sierra Norte (Oaxaca); Transnationalism; Urban Zapotec Indians -- California -- Los Angeles; Sierra Norte (Oaxaca, Mexico) -- Social life and customs; Zapotèques -- Californie -- Los Angeles -- Conditions sociales; Zapotèques -- Mexique -- Sierra Norte (Oaxaca) -- Conditions sociales; Internet et autochtones -- Californie -- Los Angeles; Internet et autochtones -- Mexique -- Sierra Norte (Oaxaca); Communication et culture -- Californie -- Los Angeles; Communication et culture -- Mexique -- Sierra Norte (Oaxaca); Transnationalisme; SOCIAL SCIENCE / Ethnic Studies / American / Hispanic American Studies; SOCIAL SCIENCE / Media Studies; SOCIAL SCIENCE / General; Communication and culture; Internet and indigenous peoples; Manners and customs; Mixe Indians -- Social conditions; Transnationalism; Urban Zapotec Indians; Zapotec Indians -- Social conditions; California -- Los Angeles; Mexico -- Sierra Norte (Oaxaca); california, mexican, latino, latina, latinx, Hispanic, immigration, migration, emigration, expat, undocumented, illegal immigration, Oaxaca, oaxacan, Zapotec, Ayuujk, indigenous, native, sierra norte, race, ethnicity, culture, racism, xenophobia, discrimination, anthropology; Electronic books